Bahan Bantu Mengajar (BBM) dalam Pengajaran dan Pembelajaran (P&P) di Sekolah Menengah Kebangsaan (SMK) Daerah Pontian - Abd Samad, Noorazman; Wan Ahmad, Wan Mohd Rashid; Harun, Hairuddin; Amiruddin, Mohd Hasril; Hashim, Suhaizal; Ja’apar, Faizah binti (Penerbit UTHM, 2018)
The use of teaching aids (BBM) in Teaching and Learning (P&P) processes is very important for teachers to ensure that the delivery of information related to the subjects taught is more clear, systematic and better for students to follow. The purpose of this study was to examine the extent of teachers’ use of BBM in P&P in four secondary schools of the Pontian district in terms of practice, skills and attitudes and differences based on teachers' gender in these three aspects. The study involved 198 respondents consist teachers, of SMK Sri Tanjung, SMK Benut, SMK Ayer Baloi and SMK Parit Betak in the Pontian district. The design of this study is a survey. This study was carried out using a questionnaire as a research instrument and the data were analyzed descriptively and inferred. Data analysis is processed using the Statistical Packages for Social Sciences for Windows Version 17.0 (SPSS) software and the findings are reported in the form of mean, standard deviation, percentage and T-Test Independent tests. The findings show that the use of teachers to BBM in P&P from all three aspects is at high level in the practice aspect (mean score 3.89), skill aspect (mean score 3.86) and attitude aspect (mean score 3.86). While T-Test Independent tests results showed that there was no significant difference base on teachers gender towards the use of BBM in the P&P process; in the practice aspect (P> 0.05 = 0. 803), skill aspect (p>0.05=0.518 ) and attitude aspect (p>0.05=0.447). Overall, teachers need to realize that the use of BBM in P&P is important to attract and improve student performance as well as achieve the teaching objectives of a subject.